Noise exposure and hearing health: a study of baristas’ perception, knowledge, and attitudes in Malaysian speciality coffee shops - Ismail, Noraidah; Ahmad Kamely, Afifah (IIUM Press, 2025)
Background: Noise-induced hearing loss (NIHL) is a significant occupational health issue globally, with service industry workers, including baristas, often overlooked despite their exposure to potentially hazardous noise levels. Objectives: This study aimed to measure noise levels in speciality coffee shops within the Kuantan municipality area and evaluate baristas’ knowledge, attitudes, and perceptions of noise and its impacts. Method: Noise levels were assessed using the NIOSH Sound Level Meter App during typical workdays, while baristas (n = 30) completed questionnaires structured around the Health Belief Model. Results: Noise levels measured in the cafés were within permissible limits. Baristas predominantly perceived noise as enhancing workplace ambience, with limited awareness of its adverse effects. Notably, none of the baristas reported ever using hearing protection devices (HPDs), highlighting a critical gap in preventive practices. Gender differences were observed in perceived susceptibility to hearing loss, with females reporting significantly higher scores than males (p = 0.02). However, no significant gender differences were found in other health belief domains. Conclusion: These results highlight the need for targeted educational interventions to raise awareness of noise hazards and promote safer work practices among baristas. The study contributes to the broader understanding of occupational health in non-industrial sectors, highlighting the importance of addressing noise exposure in the growing speciality coffee industry.